Pediatric Neurologists' Perspectives on Sexual and Reproductive Health Care for Adolescent and Young Adult Women With Epilepsy and Intellectual Disability. (January 2022) - Kirkpatrick, Laura; Collins, Amy; Harrison, Elizabeth; Miller, Elizabeth; Patterson, Christina; Sogawa, Yoshimi; Van Cott, Anne C.; Kazmerski, Traci M.
Objective: To explore perspectives of pediatric neurologists regarding sexual and reproductive health care for adolescent women with epilepsy (WWE) and intellectual disability. Methods: We interviewed pediatric neurologists regarding sexual and reproductive health for WWE with intellectual disability. We audio-recorded and transcribed interviews and conducted qualitative analysis. Results: 16 pediatric neurologists participated. Themes included the following: (1) Pediatric neurologists have differing perspectives about how intellectual disability affects WWE's sexual and reproductive health needs, (2) pediatric neurologists provide sexual and reproductive health counseling variable in content and frequency to this population, (3) pediatric neurologists tend to recommend longer-term methods of contraception for this population, and (4) pediatric neurologists are asked to be involved in decision-making around sterilization, yet express ethico-legal reservations. Conclusion: Our findings suggest pediatric neurologists provide variable, often suboptimal, sexual and reproductive health care for WWE and intellectual disability. Themes reveal ethical concerns among neurologists about sexual and reproductive health practices including sterilization. More tailored clinical guidelines and provider training on sexual and reproductive health for this population may be beneficial.